Calculation method for internal force and deformation of the prestressed I-beam on the elastic foundation - Ye, Yangsheng; Wei, Shaowei; Cai, Degou; Yang, Jianmin; Wei, Peiyong; Yue, Cuihong; Wu, Shangrui (Frontiers in Earth Science, 2023)
The elastic foundation beam theory has been widely used in civil engineering, including railway, tunnel, and building foundations. With the development of fabricated structures, more elastic foundation beams need to be prestressed. In order to explore the frame foundation beam with the fabricated anchor-cable in the slope reinforcement project, in this article, prestress is applied to both ends of the beam. Then, according to the calculation method of internal force and deformation of the beam under concentrated force and the equivalent load theory of the prestressed structure, three new methods: the finite difference method (FDM) of the Euler–Bernoulli beam on the Winkler foundation, FDM of the Euler–Bernoulli beam on the Pasternak foundation, and theoretical analytical solution of the Timoshenko beam on the Winkler foundation, are deduced to calculate internal force and deformation under prestress force and concentrated force, respectively. Typical calculation parameters are selected for design and verification via the three new methods and GEO5, respectively. The results show that the calculated values of the three new methods are basically consistent with those calculated using GEO5 software, which verifies the feasibility of the three new methods.